Mechanical Properties of Polyethylene-Carbon Nanotube Composites Synthesized by In Situ Polymerization Using Metallocene Catalysts - Mamdouh A. Al-Harthi; Bijal Kottukkal Bahuleyan (Advances in Materials Science and Engineering)
The influence of multiwalled carbon nanotubes (MWCNTs) on the properties of polyethylene prepared by in situ polymerization using metallocene catalyst (Cp2ZrCl2) in combination with methylaluminoxane has been studied. The MWCNT was incorporated in the polymer matrix adopting a stirring method. Incorporation of MWCNT causes a drop in molecular weight of the polymer along with an increase in number of branches and increase in crystallinity. It was also observed that addition of MWCNT during metallocene-catalyzed polymerization caused a drop in both the dynamic modulus and Young’s modulus of polyethylene. But the drop in tensile strength was minimal, and there was an increase in elongation at break along with consequent increase in energy at break.